Increased right ventricular uptake on (99m Tc)-sestamibi SPECT myocardial perfusion imaging as a marker of elevated pulmonary artery systolic pressure measured by Doppler echocardiography. (20th July 2021) - Sunder, V; Cha, R; Hunter, K; Dolan, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Though prior work has been done, the significance of the not uncommon finding of increased right ventricular (RV) tracer uptake in patients undergoing (99m Tc)-sestamibi SPECT myocardial perfusion imaging remains poorly defined and this finding not been systemically integrated into the interpretation of the study, despite likely carrying both diagnostic and prognostic relevance for the patient. Purpose: To examine if the presence of increased RV tracer uptake in patients undergoing myocardial perfusion imaging with same-day protocol (99m Tc)-sestamibi SPECT is associated with a higher pulmonary artery systolic pressure (PASP) measured non-invasively with transthoracic Doppler echocardiography Methods: Patients who underwent myocardial perfusion imaging with same-day protocol (99m Tc)-sestamibi SPECT at a single academic health system between 2017-2020 were retrospectively enrolled. Those patients who had a transthoracic echocardiogram performed within 60 days of the nuclear study with sufficient Doppler data to estimate pulmonary artery systolic pressure(PASP) using the tricuspid regurgitation peak velocity method were included. A right atrial pressure of either 3 mmHg, 8 mmHg, or 15 mmHg was used in the calculation of PASP in keeping with the 2015 American Society of Echocardiography guidelines. The rest images for each nuclear study were reviewed and analyzed for the presence of RV tracer uptake. RV uptake was graded as either 0 or "no RV uptake", 1+ or "partial RV uptake", or 2+ or "complete RV uptake". The nuclear studies were grouped accordingly and the mean PASP for each group was computed. The mean PASP was also computed for a combined group of patients who demonstrated either 1+ or 2+ RV uptake. Statistical analysis using a t-test was performed to compare the mean PASP of each patient group. Results: 193 patients were included in the analysis. Of those, 123(63%) demonstrated "no RV uptake", 58(31%) demonstrated 1+ or "partial RV uptake", and 12(6%) demonstrated 2+ or "complete RV uptake". 70 patients(36%) had either 1+ or 2 + RV uptake. The mean PASP was 27.2 ± 7 mmHg for the "no RV uptake" group, 28.3 ± 9 mmHg for the 1+ RV uptake group and 41. 6 ± 14 mmHg for the 2+ RV uptake group. When combined, patients demonstrating 1+ or 2+ RV uptake had a mean PASP of 30.6 ± 11 mmHg. There was no statistical difference in the mean PASP of the "no RV uptake" group and the 1+ or "partial RV uptake group" (p = 0.434). The difference in mean PASP between the "no RV uptake" group and the combined 1+ or 2+ RV uptake group was statistically significant(p = 0.028). Conclusion: In a small single health system sample, patients undergoing (99m Tc)-sestamibi SPECT myocardial perfusion imaging who have either partial or complete RV uptake on rest images have an increased pulmonary artery systolic pressure compared to patients who do not exhibit this finding.